A retórica visual do convento de São Francisco de Salvador - Beiter, Fernando Campos (2012)
The present work it is our Master research titled "The visual rhetoric of the Convent of St. Francis of Salvador - Bahia," which aims to analyze the visual discourse of the Franciscan Order of the eighteenth century through the paintings in the interior o